2005
DOI: 10.1109/tpel.2004.842977
|View full text |Cite
|
Sign up to set email alerts
|

On the Practical Design of a Sliding Mode Voltage Controlled Buck Converter

Abstract: Abstract-This paper presents a simple and systematic approach to the design of a practical sliding mode voltage controller for buck converters operating in continuous conduction mode. Various aspects of the design, including the associated practical problems and the proposed solutions, are detailed. A simple and easy-to-follow design procedure is also described. Experimental results are presented to illustrate the design procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
187
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(187 citation statements)
references
References 16 publications
0
187
0
Order By: Relevance
“…The most popular one is the hysteresis modulation (HM) method. The main advantage is that the implementation does not require additional computation or auxiliary circuitries, and it is easily accomplished by introducing a layer of hysteresis band into the signum function [65]. This method allows the switching frequency to be suppressed into a controllable form determinable by the width of the hysteresis band.…”
Section: Conventional Hysteresis Modulation Based Sliding Mode Contromentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular one is the hysteresis modulation (HM) method. The main advantage is that the implementation does not require additional computation or auxiliary circuitries, and it is easily accomplished by introducing a layer of hysteresis band into the signum function [65]. This method allows the switching frequency to be suppressed into a controllable form determinable by the width of the hysteresis band.…”
Section: Conventional Hysteresis Modulation Based Sliding Mode Contromentioning
confidence: 99%
“…It is shown that HM based SM controlled converters generally suffer from significant switching frequency variation when the input voltage and the output load are varied [20], [65]. This complicates the design of the input and output filters, and also deteriorates the regulation of the converters [66].…”
Section: The Need For Fixed-frequency Sm Controllermentioning
confidence: 99%
“…Sliding mode controller (SMC) initially used for the control of Variable structure systems, is gaining importance in the field of power electronics because of its robustness to disturbances [11,12]. Chattering problem predominant in sliding mode control is minimized by using fixed switching frequency sliding mode control as proposed in [13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of constant-frequency pulse-width modulation is widespread in switching power converters, although a sigma-delta scheme for modulation [11][12][13][14][15] and varying switching frequency schemes, such as sliding-mode and hysteretic control [16][17][18][19][20][21][22][23][24][25][26], for control can also be used. The pulse width modulation (PWM) principle is widely used in power electronics applications for controlling power converters (DC-DC, DC-AC, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hard-switching DC-DC converters, the PWM control strategy has also been applied in zero voltage (ZVS) and zero current switching (ZCS) resonant converters [28]. In many applications it is desirable to use a microcontroller, DSP or FPGA to switch a converter with the help of sophisticated control schemes such as fuzzy control [29][30][31], sliding mode control [16][17][18][19][20][21] etc. The block diagram of such a configuration is shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%